Assessment of the effects of abiotic factors related to climate change on larval stages of Pelophylax perezi - Matos, Ana Beatriz Moura Rodrigues (2019)
Climate change is a growing concern for the scientific community. For the Iberian Peninsula it is predicted that climate change driven alterations will be more profound, as well as for mountain regions. The predictable alterations will have profound implications on biota, being amphibians suggested as one of the most vulnerable classes due to their unique characteristics and high susceptibility to environmental factors. With this in mind the aim of our study was to assess the effects of climate change related abiotic factors in amphibian larvae from two distinct altitudes (low and high). To achieve this aim two different approaches were made. The first consisted in using a full factorial experimental design to assess the effects of two abiotic factors (pH and temperature) in larvae from both altitudes. The second consisted in assessing the effect of several exposure volumes/water column heights in tadpoles from high altitude which will be more prone to be affected to desiccation effect. The endpoints measured for both approaches were both morphological (size) and physiological (antioxidant defense system and peroxidative damage). From our approach the main results showed that temperature has higher influence than pH in the development time and also in the size in tadpoles, being the effects dependent on the origin (low or high altitude) of the animals. Also, the physiological parameters suggest that animals from high altitudes present higher stress to high temperatures. Furthermore, the scenario of the lowest volume/water column height (desiccation) also revealed high stress for the animals. Overall, the most relevant results of the present study, indicate that the alteration in abiotic factors, mainly temperature has influence on the development of P. perezi and that high altitude populations may be more severely affected in a scenario of climate change were temperature increases and desiccation occurs.